The Central Mechanisms of Secretin in Regulating Multiple Behaviors - Zhang, Li; Chow, Billy K. C. (Frontiers in Endocrinology, 2014)
Secretin (SCT) was firstly discovered as a gut peptide hormone in stimulating pancreatic secretion, while its novel neuropeptide role has drawn substantial research interests in recent years. SCT and its receptor (SCTR) are widely expressed in different brain regions, where they exert multiple cellular functions including neurotransmission, gene expression regulation, neurogenesis and neural protection. As all these neural functions ultimately can affect behaviors, it is hypothesized that SCT controls multiple behavioral paradigms. Current findings support this hypothesis as SCT-SCTR axis participates in modulating social interaction, spatial learning, water and food intake, motor coordination and motor learning behaviors. This mini-review focuses on various aspects of SCT and SCTR in hippocampus, hypothalamus and cerebellum including distribution profiles, cellular functions and behavioral phenotypes to elucidate the link between cellular mechanisms and behavioral control.